Politique d'évaluation des apprentissages et médiatisation d'une controverse professionnelle : ou comment la pédagogie et le « bon sens » s'affrontent - Claude Lessard; Abdoulaye Anne (Nantes Université, 2011)
This article analyzes the role of media in educational controversies. The case study is the Quebec media debate on the student evaluation policy associated with the reform of primary and secondary education programs of study, initiated in the late 90s. We identify the terms of the debate, as built by the media, and in reference to the three dimensions of legitimacy of Suchman (1995). The article illustrates the potential effects on the work of teachers of opposition to educational policies and standards set by ministerial authority, by external actors such as journalists. This analysis reveals that during the debate on the evaluation of student learning, the trial is made of the Department of education, of its precipitation and of its lack of preparation, resulting in a challenge of the pragmatic and cognitive legitimacies of the evaluation policy. But the trial is also that of an educational and moral conception of schooling. In this aspect, the debate exceeds the specific and restricted content of student evaluation and challenges a set of ideas - otherwise reduced to a caricature - which are seen as having dominated the second half of the 20th century and as being responsible for the repeated failure of systemic reforms and local attempts to improve schools.